Divorcio y su repercusión en el estado emocional de un adolescente de 13 años de edad del cantón Babahoyo - Díaz Arévalo, Alexandy Lizbeth (2023)
Divorce is the breakup or termination of a couple's marital relationship, and it occurs when the couple decides to end their relationship for various reasons, one of which may be a lack of understanding, infidelity, among other causes. Adolescents with separated parents are one of the main ones affected by divorce, since adolescents have various alterations or psychological discomforts that affect their daily lives, they can blame themselves for the situation they are experiencing within their family, they have aggressive attitudes towards their parents. and they can develop states of depression, anxiety, stress. For this reason, this case study aims to study the issue of divorce and its emotional impact on a 13-year-old adolescent from the city of Babahoyo, and aims to analyze how parental divorce affects the emotional state of a 13-year-old adolescent from the city of Babahoyo, which will be carried out through the application of different collection techniques such as; clinical history, interview, bibliographic review, application of psychometric tests such as the Beck depression inventory and the Hamilton anxiety scale, information that is organized by sessions, findings where the diagnosis of F 32.2 severe depression without psychotic symptoms, and as proposed solutions, a rehabilitation methodology is established through cognitive behavioral therapy to reduce the patient's symptoms.